0886 Relationships Between Sleep and Self-Care in Adults With Type 2 Diabetes. (27th April 2018) - Zhu, B; Bronas, U G; Quinn, L; Kapella, M C; Park, C G; Collins, E G; Ruggiero, L; Fritschi, C
Abstract: Introduction: Sleep disturbance is common in type 2 diabetes (T2D) patients and likely impairs glycemic control. Optimal glycemic control lies in daily and complex self-care. Nevertheless, sleep disturbance has been an under-examined risk factor for inadequate self-care. The purpose of this study was to examine the relationships between sleep and self-care in T2D adults. Methods: A correlational, longitudinal design was used. A convenience sample of 64 adults with T2D was recruited from a large city in the Midwestern United States. During baseline visit, validated questionnaires were administered to measure subjective sleep quality, self-care, and covariates (e.g., diabetes distress, self-efficacy, fatigue, and daytime sleepiness). Objective sleep was measured using a wrist-worn accelerometer (ActiGraph) over an 8-day period. Objective sleep parameters derived from the actigraphy included total sleep time, sleep efficiency, and number of awakenings. Bivariate correlation and separate multiple linear regression analyses were conducted to examine the relationships between sleep and self-care. Results: Participant mean age was 60.6 (SD 6.8) years (range: 50–78), and 51.6% were women. Regression analysis indicated that controlling for covariates, subjective sleep quality (beta = -0.26), diabetes distress (beta = -0.39), and daytime sleepiness (beta = -0.21) were strong predictors of self-care (R 2 = 0.51, P < 0.001). When objective sleep parameters were used, besides diabetes distress, fatigue, and daytime sleepiness, the number of awakenings (beta = -0.23) was also a significant predictor of diabetes self-care (R 2 = 0.57, P < 0.001). Conclusion: Our findings suggest that subjective sleep quality and objective nocturnal awakenings may affect self-care in older patients with T2D. Experimental studies are warranted to examine the impact of sleep interventions on diabetes self-care. Meanwhile, routine assessment and effective intervention of sleep disturbance should be further highlighted by the American Diabetes Association diabetes care guidelines. Health providers are recommended to include comprehensive sleep assessment. Support (If Any): UIC Center for Research on Health and Aging (Roybal Pilot), UIC Chancellor's Graduate Research Award, Provost's Award for Graduate Research, UIC College of Nursing Ph.D. Student Research Award, and Sigma Theta Tau Research Award.